In-vitro Study on the Effectiveness of Coconut Shell Liquid Smoke Gel on Cleaning Smear Layer and Debris in Root Canal Treatment - Setiawan, Linda Novelgia; Avrillia, Roselyn; Pradipta, Tresnandya (Journal Research of Social Science, Economics, and Management, 2025)
Smear layer and debris are major challenges in successful root canal treatment because they obstruct dentinal tubules and reduce penetration of irrigants and intracanal medicaments. Sodium hypochlorite (NaOCl) 5.25% is used; however, it has limited smear-layer removal and may induce cytotoxic effects on periapical tissues. Coconut shell liquid smoke (CS-LS) contains phenolic compounds, carbonyls, and organic acids with antibacterial and chelating properties, indicating potential as an irrigant. This study aimed to evaluate the effectiveness of CS-LS gel in removing smear layer and debris in the apical third of the root canal. This experimental study employed a post-test-only control-group design. Twenty-four single-rooted premolars were randomly allocated into four groups (n=6): 5.25% NaOCl, saline solution, CS-LS gel, and 100% CS-LS. Root canal preparation was performed up to a #25 K-file, followed by irrigation according to the assigned treatment. Specimens were examined using scanning electron microscopy at 5000× magnification. Smear layer and debris were assessed using Hülsmann’s scoring system. Statistical analysis using the Kruskal–Wallis test showed significant differences among groups for smear layer and debris scores (p=0.001). The CS-LS gel and CS-LS demonstrated lower smear layer and debris scores (1.50 ± 0.548 and 2.00±0.632) (1.83±0.408; and 2.00±0.632) than 5.25% NaOCl (4.00 ± 0.632 and 4.50 ± 0.548) and saline (3.25 ± 0.957 and 3.50 ± 0.577). Mann–Whitney analysis showed significantly lower scores for CS-LS gel compared with NaOCl 5.25% and saline (p<0.05). CS-LS gel was effective in cleaning the smear layer and debris in the apical third of the root canal